Dietary supplementation with citrus extract alters the plasma parameters, circulating amino acid profiles and gene expression of small intestinal nutrient transporters in Chinese yellow‐feathered broilers. (6th August 2020) - Yu, Miao; Li, Zhenming; Wang, Gang; Cui, Yiyan; Rong, Ting; Tian, Zhimei; Liu, Zhichang; Li, Jiazhou; Chen, Weidong; Ma, Xianyong
Abstract: BACKGROUND: This study evaluated the effects of citrus extract (CE) on growth performance, plasma amino acid (AA) profiles, intestinal development and small intestine AA and peptide transporter expression levels in broilers. A total of 540 one‐day‐old yellow‐feathered broilers were fed a basal diet without any antibiotic (control group), or a basal diet containing 10 mg kg −1 zinc bacitracin (antibiotic group), or a basal diet supplemented with 10 mg kg −1 CE (CE group). After 63 days of feeding, two broilers per pen were slaughtered to collect tissues for further analysis. RESULTS: Results showed that CE increased ( P  < 0.05) the final body weight and average daily gain from day 1 to 63, and decreased ( P  < 0.05) the feed/gain ratio from day 1 to 63. Dietary CE supplementation increased ( P  < 0.05) plasma total protein, albumin and glucose concentration, and decreased ( P  < 0.05) urea concentration. CE supplementation increased ( P  < 0.05) the villus height in the ileum and the villus height/crypt depth in the jejunum and ileum, but decreased ( P  < 0.05) the crypt depth in the jejunum and ileum. CE supplementation increased ( P  < 0.05) most plasma essential AA concentrations. Additionally, CE supplementation upregulated ( P  < 0.05) ASCT1, b 0, + AT, B 0 AT1, EAAT3, rBAT, y + LAT2 and PepT1 expression in the jejunum, and b 0, + AT, EAAT3, rBAT, y + LAT2, CAT1 and PepT1 in the ileum. CONCLUSIONS: Collectively, our results indicated that CE supplementation promotes intestinal physiological absorption of AAs by upregulating gene expression of small intestinal key AA and peptide transporters, thereby enhancing the growth performance of broilers. © 2020 Society of Chemical Industry